2020
DOI: 10.1074/jbc.aac120.012837
|View full text |Cite
|
Sign up to set email alerts
|

Correction: An ATP-competitive mammalian target of rapamycin inhibitor reveals rapamycin-resistant functions of mTORC1.

Abstract: There was an error in Fig. 4A. The immunoblot for total levels of S6K was mistakenly duplicated for both WT and rictor Ϫ/Ϫ MEFs. This error has now been corrected and does not affect the results or conclusions of this work. Figure 4A. ADDITIONS AND CORRECTIONS 2886

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Only TORC1 is highly sensitive to rapamycin, while TORC2 is either insensitive, or sensitive, to rapamycin only after long exposure to the drug [12,[20][21][22][23]. The use of rapamycin to probe mTORC1-dependent activities has played an important role in accelerating our understanding of mTORC1 signaling, although it should be borne in mind that TORC1 executes both rapamycin-sensitive and -insensitive functions [24,25]. TOR-specific ATP-competitive inhibitors that inhibit both TORC1 and TORC2 are also available and are being tested in clinical trials [26].…”
Section: Introductionmentioning
confidence: 99%
“…Only TORC1 is highly sensitive to rapamycin, while TORC2 is either insensitive, or sensitive, to rapamycin only after long exposure to the drug [12,[20][21][22][23]. The use of rapamycin to probe mTORC1-dependent activities has played an important role in accelerating our understanding of mTORC1 signaling, although it should be borne in mind that TORC1 executes both rapamycin-sensitive and -insensitive functions [24,25]. TOR-specific ATP-competitive inhibitors that inhibit both TORC1 and TORC2 are also available and are being tested in clinical trials [26].…”
Section: Introductionmentioning
confidence: 99%
“…The role of Rapamycin in inhibiting the mTOR phosphorylation had been described previously by Ballou and Lin ( 56 ), and Thoreen et al. ( 57 ) ( 56 , 58 ). We have also reported that Rapamycin inhibits phosphorylation of p-S6, which is the activation state of m-TOR and upregulated in presence of infection ( Figure 3D ).…”
Section: Discussionmentioning
confidence: 76%
“…In mammalian cells, the upstream amino acids signal through specific sensors such as GATOR2 (GAP activity towards Rags 2) which activate TOR when amino acids are abundant. In both yeast and mammals, the inactivation of TORC1 induces autophagy, even in nutrient-replete conditions, indicating that TOR negatively regulates autophagy [95][96][97].…”
Section: Upstream Regulators Of Torc1mentioning
confidence: 99%